Mulching in grape plantations - Némethy, L.; Májer, J.; Varga, P.; Németh, Cs.; Fenyvesi, L.; Szabó, I. (International Journal of Horticultural Science, 2006)
In continuous studies regarding the conservation of the advantageous condition of the soil structure, the highland plantations that are surrounded by living waters have major importance where the erosion of the soil, nutrients and chemicals endangers the quality of the water and the living world of the waters. At the same time the extreme weather and dry summers of the past years have made it important to look for soil cultivation solutions and technologies that are capable of decreasing the evaporation of the soil, for enhanced conservation of soil moisture and to improve the soil structure that is required for the growth of healthy roots. In our experiment we have studied soil mulching with organic plant residue, by sods and the effect of the mechanical cultivation on the soil and on the grape through two growing seasons. From the studied treatments, the mulching with organic plant wastage showed the most efficient results from the point of view of the nutrient distribution in the grape and yield. It also had a positive effect on the soil structure and humidity.